2022
DOI: 10.1210/clinem/dgac616
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Phosphate Homeostasis: Females Excrete More Phosphate and Calcium After an Oral Phosphate Challenge

Abstract: Context Dietary consumption of phosphate is increasing, and elevated serum phosphate is associated with increased cardiovascular disease (CVD) risk. Sex differences in phosphate homeostasis and response to changes in dietary phosphate intake, which are not captured by clinically measured analytes, may contribute to differences in CVD presentation and bone disease. Objective To assess sex differences in acute phosphate homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Furthermore, these previous studies have been carried out in men, whereas our cohort includes women. A greater excretion of P in females than in males in response to oral challenge of P has been reported [53], but any sex‐specific differences in P‐homeostasis or susceptibility to large intakes of P in relation CVD risk can only be speculated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these previous studies have been carried out in men, whereas our cohort includes women. A greater excretion of P in females than in males in response to oral challenge of P has been reported [53], but any sex‐specific differences in P‐homeostasis or susceptibility to large intakes of P in relation CVD risk can only be speculated.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated in this cohort that a higher ratio of bone resorption to bone formation biomarkers was associated with greater de novo phosphate excretion in female participants, suggesting that some excreted minerals may have originated from bone. 7 In response to dietary phosphate, females with obesity may have a protective skeletal advantage due to reduced mobilization of endogenous calcium. This is consistent with the documented association of weight loss with lower bone mass and increased bone resorption in postmenopausal females.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of measurement within this study cohort have been previously reported. 7 Jaya K. Sharma and Mandy E. Turner are shared primary contribtors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations